2008
DOI: 10.1002/anie.200803242
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Component Liquid Crystals as Chiral Reaction Media: Highly Enantioselective Photodimerization of an Anthracene Derivative Driven by the Ordered Microenvironment

Abstract: Tailored to the reaction: Within a liquid‐crystalline matrix provided by a chiral amphiphilic amino alcohol, the photodimerization of an anthracenecarboxylic acid proceeds with high probability and with excellent regio‐, diastereo‐, and enantioselectivities (up to 81 % ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 52 publications
0
47
1
4
Order By: Relevance
“…20 It is also considered that the dimers D-2COOH form hydrogen bonding with two carboxylic acid groups of the neighboring photodimers, which promote segregation of the crystals in IL. It is to note that the photodifferentiation phenomenon found in this study has not been reported for the previous [4+4] cycloaddition reaction of anthracene carboxylic acids in organogels, 12,21 liquid crystals, 22,23 and ionic liquids, 24,25 probably due to the presence of organic solvents or the use of 2-anthracenecarboxylate, whose pK a is less influenced by photodimerization.…”
contrasting
confidence: 62%
“…20 It is also considered that the dimers D-2COOH form hydrogen bonding with two carboxylic acid groups of the neighboring photodimers, which promote segregation of the crystals in IL. It is to note that the photodifferentiation phenomenon found in this study has not been reported for the previous [4+4] cycloaddition reaction of anthracene carboxylic acids in organogels, 12,21 liquid crystals, 22,23 and ionic liquids, 24,25 probably due to the presence of organic solvents or the use of 2-anthracenecarboxylate, whose pK a is less influenced by photodimerization.…”
contrasting
confidence: 62%
“…3 Such an orientation can be controlled using directional supermolecular interactions such as hydrogen bonding and π-π stacking. 4 To induce the reversible crystalline phase reaction, we focused on the hexanuclear cluster [ 3 ] -anion. Each Fe II is further coordinated with one acetonitrile and two water molecules.…”
mentioning
confidence: 99%
“…43,44 The [4+4] photodimerization of 2 -anthracenecarboxylate (AC) accommodated in γ -CD and its derivatives was investigated in detail. 45 Inoue and co -workers have recently reinvestigated the photodimerization of AC from the chiral point of view by using a variety of chiral hosts. γ -CD forms very stable 1 : 2 host -guest complex with AC in aqueous buffer solution with association constants of K 1 = 160 M − 1 and K 2 = 38500 M − 1 .…”
Section: Unimolecular Reactionsmentioning
confidence: 99%